2020
DOI: 10.1007/s11655-020-3426-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an Integrative Therapy for Treating COVID-19: A Randomized Controlled Trial

Abstract: In December 2019, a number of patients with a new type of pneumonia of unknown etiology were detected in Wuhan, China. (1) It was then soon determined that it was a new severe acute respiratory syndrome (SARS) that was caused by a new coronavirus, the SARS-CoV-2 virus. (2) The new pneumonia was later named the Novel 2019 Coronavirus or COVID-19. (3) In 2002-2003, another SARS-causing coronavirus, the SARS-CoV virus, caused one of the most deadly epidemics in recent history. The outbreak of SARS-CoV caused more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 25 publications
(31 reference statements)
1
77
0
Order By: Relevance
“…In terms of the random sequence generation methods of the included 10 RCTs, six RCTs (Fu et al, 2020a;Wang et al, 2020c;Duan et al, 2020;Qiu et al, 2020;Sun et al, 2020;Yu et al, 2020) used random number tables, two trials (Ding et al, 2020;Ye, 2020) used a simple random allocation method and the remaining two RCTs (Zhang et al, 2020a;Fu et al, 2020b) only mentioned random without describing the detailed randomization method. Two RCTs (Wang et al, 2020c;Ye, 2020) performed allocation concealment. Therefore, the risk of selection (allocation) bias was unclear for the majority of the included RCTs due to lack of information on allocation concealment.…”
Section: Methodological Quality Of Rctsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of the random sequence generation methods of the included 10 RCTs, six RCTs (Fu et al, 2020a;Wang et al, 2020c;Duan et al, 2020;Qiu et al, 2020;Sun et al, 2020;Yu et al, 2020) used random number tables, two trials (Ding et al, 2020;Ye, 2020) used a simple random allocation method and the remaining two RCTs (Zhang et al, 2020a;Fu et al, 2020b) only mentioned random without describing the detailed randomization method. Two RCTs (Wang et al, 2020c;Ye, 2020) performed allocation concealment. Therefore, the risk of selection (allocation) bias was unclear for the majority of the included RCTs due to lack of information on allocation concealment.…”
Section: Methodological Quality Of Rctsmentioning
confidence: 99%
“…Two RCTs (Wang et al, 2020c;Ye, 2020) performed outcome assessor blinding and the remaining eight RCTs (Fu et al, 2020a;Zhang et al, 2020a;Fu et al, 2020b;Ding et al, 2020;Duan et al, 2020;Qiu et al, 2020;Sun et al, 2020;Yu et al, 2020) did not report relevant information, thus the detection bias for the majority of the included RCTs was judged as unclear-risk. In terms of attrition bias, eight RCTs (Fu et al, 2020a;Zhang et al, 2020a;Wang et al, 2020c;Ding et al, 2020;Duan et al, 2020;Qiu et al, 2020;Sun et al, 2020;Ye, 2020) were assessed as low-risk of bias due to complete outcome data or incomplete outcome data being adequately addressed, two RCTs (Fu et al, 2020b;Yu et al, 2020) were assessed as high-risk due to incomplete outcome data that were not adequately addressed. Two RCTs (Wang et al, 2020c;Ye, 2020) registered the study protocol and reported the registration information.…”
Section: Methodological Quality Of Rctsmentioning
confidence: 99%
See 3 more Smart Citations